The Effect of Organizational Commitment and Organizational Culture on Employee Performance With Job Satisfaction as an Intervening Variable at the Personnel and Human Resource Development Agency (BKPSDM) Padang - Ana Frehesti; John Veri (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the influence of organizational commitment and organizational culture on employee performance, with job satisfaction as an intervening variable, at the Padang Human Resources Development and Personnel Agency (BKPSDM). Data collection methods were conducted through surveys and questionnaires, with a sample of 73 respondents. The analysis method used was structural equation modeling using SmartPLS. The research results show a significant influence of segmentation on purchasing interest. There is a significant influence of organizational commitment on job satisfaction. There is a significant influence of organizational culture on job satisfaction. There is a significant influence of organizational commitment on employee performance. There is a significant influence of organizational culture on employee performance. There is a significant influence of job satisfaction on employee performance. There is a significant influence of organizational commitment on employee performance through job satisfaction. There is a significant influence of organizational culture on employee performance through job satisfaction.